Bis(bipyridine) ruthenium(ii) bis(phosphido) metalloligand: synthesis of heterometallic complexes and application to catalytic (E)-selective alkyne semi-hydrogenation. Issue 4 (13th December 2018) - Takemoto, Shin; Kitamura, Manami; Saruwatari, Shuhei; Isono, Atsutaka; Takada, Yoko; Nishimori, Rie; Tsujiwaki, Mina; Sakaue, Naoki; Matsuzaka, Hiroyuki
Abstract : The first (bpy)2 Ru(ii ) phosphido complex serves as an effective bidentate metallophosphine ligand to generate catalytically active heterobimetallic species. Abstract : The first phosphido derivative of the bis(bipyridine) ruthenium(ii ) fragment, cis -[(bpy)2 Ru(PPh2 )2 ] ([RuP2 ]), has been developed and applied as a P-donor metalloligand to form new Ru–Rh, Ru–Ir and Ru2 Cu2 heterometallic complexes. The Ru–Ir hydride complex [([RuP2 ])IrH(NCMe)3 ][BF4 ]2 exhibits significant catalytic activity for ( E )-selective semi-hydrogenation of alkynes.